Endocrine cells in diffuse pulmonary fibrosis. Issue 12 (December 1993) - Wilson, N J; Gosney, J R; Mayall, F
Abstract : BACKGROUND--There is evidence to suggest, particularly from studies in animals, that the products of pulmonary endocrine cells, especially gastrin releasing peptide, may have a role in the pathogenesis of fibrosis in the lung. This study was carried out to examine the morphology, number, distribution, and content of pulmonary endocrine cells in tissue from 49 patients with diffuse pulmonary fibrosis. METHODS--Twenty patients with interstitial pneumonitis, 17 with early fibrosis, and 12 with frank honeycombing were studied, together with five age matched controls without pulmonary disease. Endocrine cells were immunolabeled by the avidin-biotin complex method for two general markers (protein gene product 9.5 and neuron specific enolase) and a range of normal and aberrant secretory products. RESULTS--In the early stages, characterised by vigorous pneumonitis, endocrine cells were normal in appearance and distribution but very few in number. They contained only those secretory products normally found in such cells in health; inappropriate substances were not seen. By the time of early fibrosis endocrine cells were even fewer. None were identifiable in the lungs affected by honeycombing, despite the fact that all contained intact, well preserved epithelium. CONCLUSIONS--It seems unlikely that the products of pulmonary endocrine cells can have any role in the pathogenesis of diffuse pulmonary fibrosis in man, the diminution in their number with advancing fibrosis probably reflecting their loss simply as a consequence of generalised epithelial damage.